2019
DOI: 10.1002/ps.5567
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow across host‐associated populations of the rice stem borer Chilo suppressalis Walker (Lepidoptera: Crambidae): implications for Bt resistance management in rice

Abstract: BACKGROUND: The rice stem borer, Chilo suppressalis, is a serious pest of rice, but also damages an aquatic vegetable, water oats (Zizania latifolia Turcz.). The time at which mating occurs is different between populations of rice stem borer associated with rice and those associated with water-oats, which suggests that undetected cryptic species may be associated with these plant hosts. If true, this would have significant management implications. This study is the first empirical test of this idea, using popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that comparisons of differences in agronomic traits ( Xia et al, 2011 ; Wang et al, 2012a ; Li et al, 2013 ; Jiang et al, 2016 ), nutritional composition ( Wang et al, 2012b ; Jian et al, 2014 ; Jiang et al, 2018 ; Takeda et al, 2019 ), environmental adaptability ( Jiang et al, 2018 ; Wang et al, 2019 ; Park et al, 2019 ), gene transcription, protein expression, and metabolite levels ( Liu et al, 2012 ; Liu Y. et al, 2015 ; Fu et al, 2019 ; Peng et al, 2019 ) among transgenic crops and their parents are important means and strategies for confirming and excluding the unintended effects of transgenic crops, in addition to facilitating any safety evaluations. However, the molecular mechanisms of underlying the unintended effects observed in transgenic crops are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that comparisons of differences in agronomic traits ( Xia et al, 2011 ; Wang et al, 2012a ; Li et al, 2013 ; Jiang et al, 2016 ), nutritional composition ( Wang et al, 2012b ; Jian et al, 2014 ; Jiang et al, 2018 ; Takeda et al, 2019 ), environmental adaptability ( Jiang et al, 2018 ; Wang et al, 2019 ; Park et al, 2019 ), gene transcription, protein expression, and metabolite levels ( Liu et al, 2012 ; Liu Y. et al, 2015 ; Fu et al, 2019 ; Peng et al, 2019 ) among transgenic crops and their parents are important means and strategies for confirming and excluding the unintended effects of transgenic crops, in addition to facilitating any safety evaluations. However, the molecular mechanisms of underlying the unintended effects observed in transgenic crops are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molecular data can be used to trace pest dispersal routes and to infer whether gene flow occurs between populations (Franklin et al, 2011; Li et al, 2015; Otim et al, 2018). This has practical significance, e.g., regarding the spread of mutations affecting fitness and the effectiveness of refuge crops to delay evolution of Bacillus thuringiensis Berliner (Bt) resistance (Miller & Sappington, 2017; Wang et al, 2020). In this context, mitochondrial DNA (mtDNA) has proven useful for species identification and for population genetic studies, because of its maternal inheritance, relatively high mutation rates, and low recombination rates (Avise et al, 1987; Galtier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Species complexes, composed of a group of closely related species, often lack morphological characters for species identification, which can lead to shortcomings in our understanding of a specific insect's biology and impede the development of new strategies to manage pests [4][5][6][7][8][9]. Misidentification of pest species can reduce the effectiveness of management programs targeting plant and human diseases vectors [5,8], slow the advancement of biological control efforts [6] and potentially increase grower dependency on the prophylactic use of insecticides.…”
Section: Introductionmentioning
confidence: 99%